Komunikasi Pemasaran Destinasi Wisata Situ Gunung Suspension Bridge Sukabumi Pasca Pandemi - Anne Sandra Dewi; Rosita Juliyanti (STISIP Widyapuri Mandiri Sukabumi, 2025)
Marketing communication activities are very diverse and growing rapidly to this day. Effective marketing is the spearhead for the development of the tourism business, especially when competition in the development of the tourism business shows an increasingly high identity with various products and new tourist destinations in this industry. In fact, not a few business people in the tourism industry failed and went out of business because they were unable to carry out their marketing activities effectively. PT. Fontis Aquam Vivam designs the most appropriate, efficient and effective marketing communications to make it easier for management to determine how marketing will be carried out.This research uses a qualitative approach with descriptive methods. Data collection techniques using observation techniques, interviews, documentation and triangulation techniques. Then analyze the data by reducing data, presenting data, and drawing conclusions. As for the research informants there were 5 people, using a purposive sampling technique.The results of this study indicate that Fontis Aquam Vivam uses 6 dimensions in marketing communications, namely, Advertising, Personal Selling, Direct Marketing, Sales Promotion, Public Relations and Publicity, Interactive marketing. Based on the data obtained in the field, it shows that not all dimensions run well, there are several dimensions that do not work and are not implemented by PT. Aquam Vivam font.